2019
DOI: 10.1186/s40729-019-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ appreciation of pre-implant augmentation of the severely resorbed maxilla with calvarial or anterior iliac crest bone:a randomized controlled trial

Abstract: Background Little is known about the impact of bone graft harvesting for pre-implant augmentation of the maxilla from a patient’s perspective. To assess patient-reported outcome measures (PROMs) related to augmentation of the extremely resorbed edentulous maxilla with calvarial or anterior iliac crest bone. Materials and methods For this randomised controlled trial, 20 consecutive edentulous patients needing extensive pre-implant sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…MSFA with autogenous bone graft used alone or in combination with different ratios of bone substitutes generates more newly formed bone, higher bone-toimplant contact, and earlier bone formation compared with the use of a bone substitute alone [13,[29][30][31]. However, harvesting of extraoral and intraoral autogenous bone graft negatively influences postsurgical OHRQoL due to increased pain, impaired eating and speaking ability, sleep impairment, limitation in daily routine, and sick leave [12,[32][33][34]. Patient's perception of recovery is therefore strongly associated with the surgical procedure, absence of pain, rapidly recovery of oral function and return to normal lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…MSFA with autogenous bone graft used alone or in combination with different ratios of bone substitutes generates more newly formed bone, higher bone-toimplant contact, and earlier bone formation compared with the use of a bone substitute alone [13,[29][30][31]. However, harvesting of extraoral and intraoral autogenous bone graft negatively influences postsurgical OHRQoL due to increased pain, impaired eating and speaking ability, sleep impairment, limitation in daily routine, and sick leave [12,[32][33][34]. Patient's perception of recovery is therefore strongly associated with the surgical procedure, absence of pain, rapidly recovery of oral function and return to normal lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Calvarial bone can be harvested safely and has been shown to be accompanied by minor morbidity with low direct postoperative pain levels. The patient-reported outcome measures confirmed that bone graft harvesting from the calvarium is an appropriate procedure, reflected by high levels of satisfaction, minor long-term sequela and improvement of perceived oral health [5]. A limitation of calvarial bone harvesting may be visible scarring in the bald patient, and possible contour deficits afterwards [5].…”
Section: Discussionmentioning
confidence: 77%
“…Calvarial bone grafts can serve as an alternative to anterior iliac crest bone grafts. Major advantages of harvesting calvarial bone is the lower early donor site morbidity [4,5] and less resorption of the bone graft during follow-up [6]. A limitation is possible scar visibility in bald patients or palpable contour deficits [5].…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the remaining 76 reports were screened and subsequently 43 reports were included. Among these, three articles included data from studies described in other articles as well 17,18,30,31,34,35 ; thus the data from both reports were combined. Finally, 40 studies were included for data collection and quality assessment (Fig.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…The techniques used for calvarial harvesting were similar to that described by Tessier, 59 Kellman, 60 and Schortinghuis. 5,10,[16][17][18] The information on the prevention of intracranial perforations and filling of the contour defect varied. The calvarial defects were repaired by means of synthetic bone substitutes, such as polymethyl methacrylate (PMMA) 17,19,43 or titanium mesh or calcium phosphate cement.…”
Section: Study Characteristics and Interventionsmentioning
confidence: 99%